A Brief History of Child Psychoanalytic Training. Issue 1 (31st December 2022) - Meersand, Pamela
ABSTRACT: This paper traces the history of child psychoanalytic education, with emphasis on Anna Freud's vision of training as inseparable from observation and research, from the issues of children's education and upbringing, and from service to marginalized families. Historical obstacles to the formalization of child training – lack of parity for non-medical practitioners, organizational hierarchies, negative attitudes toward child work – are reviewed, as well as the pathways by which leaders in the field ultimately surmounted these hindrances, allowing child psychoanalytic centers to develop and create novel training models. In conclusion, the author draws from this complex history to propose a number of potential future directions that might help revitalize contemporary training programs.